2015
DOI: 10.1007/s11842-015-9293-y
|View full text |Cite
|
Sign up to set email alerts
|

The Quest for Sustainable and Decentralized Forest Governance in Eastern Cameroon: The Dimako Council Forest Case Examined

Abstract: In the last three decades, with the increasing threat of environmental degradation and indigenous calls for involvement in the governance of natural resources, decentralization policies have been implemented globally in the hope that the participation of rural communities and governments will help improve the conservation of those resources. It is partly under this assumption that, in recent years, an increasing number of local council forests are being created in Cameroon's forest regions. Using semi-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In a study in Uganda, Galabuzi et al [95] reported that the conditionalities for farmers to participate in forest restoration schemes included assuring them secure access to forest resources and equitable benefit sharing. Ofoulhast-Othamot [98] highlighted the shortcomings of local participation when the conditions are not propitious. Local participation in community forest management in Dimako, Eastern Province of Cameroon, was deemed ineffective due to poor implementation by local officials, lack of accountability, and inconsistencies in implementation against project objectives.…”
Section: Managerial Aspects At the Project/program Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study in Uganda, Galabuzi et al [95] reported that the conditionalities for farmers to participate in forest restoration schemes included assuring them secure access to forest resources and equitable benefit sharing. Ofoulhast-Othamot [98] highlighted the shortcomings of local participation when the conditions are not propitious. Local participation in community forest management in Dimako, Eastern Province of Cameroon, was deemed ineffective due to poor implementation by local officials, lack of accountability, and inconsistencies in implementation against project objectives.…”
Section: Managerial Aspects At the Project/program Levelmentioning
confidence: 99%
“…Davies [97] further took a local perspective on governance and divided community engagement into local participation in decision-making, compliance with laws and rules, and empowerment. However, Ofoulhast-Othamot [98] also cautioned that local participation does not always result in ab improvement in natural resource governance and conservation if compliance and enforcement are poor. Davies [97] stressed the greater benefits that stem from strengthening governance, emphasizing the two-way influence that governance and tenure security and rights have on each other.…”
Section: Governance-related Factorsmentioning
confidence: 99%
“…Moreover, the lack of focus on the key developmental objectives of council forests seems to have carried on into the governance of the forest itself. It transpires that from 2004 municipal authorities had bypassed the restrictions imposed by the management plan and engaged in logging practices that called into question the long‐term sustainability of the FCD (Om Bilong et al., ; Ofoulhast‐Othamot, ). This happened in large part because local mechanisms designed to involve the forestry administration, municipal authorities and village representatives in monitoring the implementation of the FCD management plan essentially collapsed in the face of elite capture (Singer, ; Cuny, ; Ofoulhast‐Othamot, ).…”
Section: The Dimako Council Forest Case Studymentioning
confidence: 99%
“…This article builds on that literature by examining the dual processes of devolution of power to municipalities and municipal forest governance in Cameroon. On the one hand, although the literature on council forests is still developing, numerous studies have already begun to show the negative outcomes associated with municipal forest governance on both the utilization of forest revenues and the sustainability of those forests (Om Bilong, Zongang Ngongang, Kaffo Nzouwo, Ondoua, & Nguenang ; Cuny, ; Kouna Eloundou, ; Ofoulhast‐Othamot, , ; Zamedjo; ). On the other hand, despite its status as forerunner in forest policy reform in the Congo basin, the locus of global efforts to protect Africa's tropical rainforests, no extant study has fully examined the connection between the political and sectoral forest management decentralizations in Cameroon.…”
Section: Introductionmentioning
confidence: 99%